The Research Analyst and Development Tax Evasion: A Literature Review - Sartono Sartono (Sekolah Tinggi Ilmu Ekonomi Al-Madani, 2026)
This review synthesizes evidence from 95 international journal articles published between 2020 and 2025 to examine interrelationships among tax morale, agency problems, institutional quality, sustainability pressure, and ESG disclosure. The literature consistently shows that high tax morale, rooted in ethical awareness and strong social norms, significantly reduces opportunistic behavior and enhances tax compliance among individuals and corporations. However, agency problems remain persistent. Misalignment between managers and stakeholders often leads to reduced transparency, earnings management, and aggressive tax avoidance, particularly in environments with weak institutional frameworks. Strong institutional quality, characterized by effective regulation, sound governance mechanisms, and credible enforcement, plays a critical role in mitigating agency costs and strengthening the reliability of ESG disclosures. Simultaneously, growing pressure from regulators, investors, and civil society for sustainable business practices encourages firms to improve the scope and credibility of ESG reporting. Enhanced ESG disclosure.